Prevalence of Chronic Obstructive Pulmonary Disease and Chronic Bronchitis Among Predominantly Smoking Workers in the Seafood Industry in Greenland - Frederiksen,Anja Lærke; Laustsen,Birgitte Hamann; Bælum,Jesper; Pedersen,Michael Lynge; Bønløkke,Jakob Hjort (International Journal of Chronic Obstructive Pulmonary Disease, 2022)
Anja Lærke Frederiksen,1 Birgitte Hamann Laustsen,2,3 Jesper Bælum,4 Michael Lynge Pedersen,1,3 Jakob Hjort Bønløkke5 1Steno Diabetes Center Greenland, Nuuk, Greenland; 2Department of Clinical Medicine, Faculty of Medicine, Danish Ramazzini Centre, Aalborg University, Aalborg, Denmark; 3Greenland Center for Health Research, Institute of Nursing and Health Science, University of Greenland, Nuuk, Greenland; 4Research Unit for General Practice, Department of Public Health, University of Southern Denmark, Odense, Denmark; 5Department of Occupational and Environmental Medicine, Danish Ramazzini Centre, Aalborg University Hospital, Aalborg, DenmarkCorrespondence: Jakob Hjort Bønløkke, Department of Occupational and Environmental Medicine, Danish Ramazzini Centre, Aalborg University Hospital, Havrevangen 1, Aalborg, 9000, Denmark, Tel + 45 97664109, Email jahb@rn.dkIntroduction: For decades, the prevalence of smoking has been high in Greenland. Even so, the prevalence of chronic obstructive pulmonary disease (COPD), a smoking-related disease, remains largely unexplored. This cross-sectional study aimed to estimate the prevalence of COPD and chronic bronchitis (CB) among Inuit workers in the seafood industry in Greenland.Methods: A total of 355 participants, 254 males and 101 females, met the inclusion criteria. Participants had a mean age of 38 years (standard deviation 13.5; range 17– 68 years). COPD was diagnosed based on post-bronchodilator ratio between forced expiratory volume within one second and forced vital capacity (FEV1/FVC) below the lower limit of normal (LLN) according to the Global Lung Function Initiative. Participants completed a questionnaire aiming to diagnose CB.Results: The overall prevalence was 9.9% for COPD; 7.4% for CB. Participants were predominantly smokers; 73.2% active smokers, 91.8% active or former smokers. The prevalence of COPD was high, especially among those under 40 years of age. Both COPD and CB were associated with smoking status.Discussion: This study among Greenlandic ...